Days - Cai, Mingliang 1957-; Chang, Jhong-Yuan; Lai, Tian-Jian; Lee, Kang-Sheng 1968-; Anong, Houngheuangsy (Second run, 2024)
"Days" is Tsai Ming-Liang's meditation on solitude, delivered as a series of beautifully composed, delicately hued tableaux. The uneventful lives of two men unfold until they eventually cross paths, brought together out of loneliness and the need for intimacy. "Afternoon" captures a wide-ranging and absorbing conversation between director Tsai and Lee Kang-Sheng, the actor, collaborator, friend and muse who has appeared in all of Tsai's films, as they reflect upon their lives, careers, friendship and identity." [secondrundvd.com]
Original: Taiwan, Frankreich 2020
Original: Taiwan 2015
Two-film, two-disc special edition Blu-ray: presented from director-approved HD masters ; a filmed interview with Tsai Ming-Liang (2022) ; Wandering (2021): a short film reflecting director Tsai's 'Walker' art installation project ; Tsai Ming-Liang in conversation with Tony Rayns at the East Asia Film Festival Ireland, 2019 ; Days passed: Lee Kang-Sheng through the eyes of Tsai Ming-Liang: a video essay by writer Michelle Cho ; 20-page booklet with a new essay by writer So Mayer ; 5.1 DTS-HD Master Audio option on Days
Bildformat 1.85:1
Keywords: Film; Blu-Ray-Disc